The effect of investment knowledge, eco-friendly lifestyle, and interest rates on investment interest among millennials and gen Z - Amanda, Ferdita; Suhardi; Akbar, Jufrisani; Adriana, Nana (PT Mattawang Mediatama Solution, 2025)
This study aims to analyze the influence of investment knowledge, environmentally friendly lifestyles, and interest rates on investment interest among Generation Z. The study results show that investment knowledge significantly impacts investment interest, where higher financial literacy encourages more rational and informed investment decisions. An environmentally friendly lifestyle also contributes to increasing investment interest, although its influence is not as strong as financial literacy. Interest rates are proven to affect investment decisions, but their contribution is smaller compared to other factors. These findings indicate that a combination of good financial literacy and awareness of sustainable investment can enhance Generation Z's participation in the investment world. Therefore, financial education and the promotion of sustainability-based investment need to be improved to encourage wiser and more responsible investment decisions.